CCl4 inhibits the expressions of hepatic taurine biosynthetic enzymes and taurine synthesis in the progression of mouse liver fibrosis. (12th October 2022) - Zhang, Di; Zheng, Jiaming; Qiu, Guobin; Niu, Tongjuan; Gong, Yuneng; Cui, Sheng
Carbon tetrachloride (CCl4 ) is a widely used hepatotoxin for the studies of liver fibrosis and cirrhosis, and taurine has function to abate liver fibrosis induced by CCl4 . But the interacting mechanisms between taurine and CCl4 in liver are still largely unknown. These made us to hypothesize that CCl4 may induce liver fibrosis by affecting the expressions of taurine biosynthetic enzymes and taurine synthesis. We thus assayed the expressions of hepatic cysteine dioxygenase (CDO), cysteine sulfonate acid decarboxylase (CSAD) and taurine transporter (TauT) in the progression of mouse liver fibrosis induced by CCl4 . The results demonstrated that CCl4 treatment markedly decreased hepatic CSAD, CDO expressions, and taurine levels in hepatic tissue, although TauT expression did not exhibit significant decline. It was contrasting that hepatic α-SMA, serum AST, ALT, ALP kept increasing, which were accompanied by the pathological characters of liver, whereas taurine supplement attenuated the progression of liver fibrosis induced by CCl4 . These results demonstrate that CCl4 may induce liver fibrosis by inhibiting hepatic CSAD and CDO expressions and taurine synthesis, which are crucial for our understanding the mechanisms of liver fibrosis induced by CCl4, and also potential for establishing therapeutic strategies of liver fibrosis and related diseases.